A high-density linkage map and QTL mapping of fruit-related traits in pumpkin (Cucurbita moschata Duch.). Issue 1 (December 2017) - Zhong, Yu-Juan; Zhou, Yang-Yang; Li, Jun-Xing; Yu, Ting; Wu, Ting-Quan; Luo, Jian-Ning; Luo, Shao-Bo; Huang, He-Xun
Abstract Pumpkin (Cucurbita moschata ) is an economically worldwide crop. Few quantitative trait loci (QTLs) were reported previously due to the lack of genomic and genetic resources. In this study, a high-density linkage map ofC. moschata was structured by double-digest restriction site-associated DNA sequencing, using 200 F2 individuals of CMO-1 × CMO-97. By filtering 74, 899 SNPs, a total of 3, 470 high quality SNP markers were assigned to the map spanning a total genetic distance of 3087.03 cM on 20 linkage groups (LGs) with an average genetic distance of 0.89 cM. Based on this map, both pericarp color and strip were fined mapped to a novel single locus on LG8 in the same region of 0.31 cM with phenotypic variance explained (PVE) of 93.6% and 90.2%, respectively. QTL analysis was also performed on carotenoids, sugars, tuberculate fruit, fruit diameter, thickness and chamber width with a total of 12 traits. 29 QTLs distributed in 9 LGs were detected with PVE from 9.6% to 28.6%. It was the first high-density linkage SNP map forC. moschata which was proved to be a valuable tool for gene or QTL mapping. This information will serve as significant basis for map-based gene cloning, draft genome assembling and molecular breeding.